PREVALENCE AND QUALITY OF LIFE OF PEMPHIGUS PATIENTS AT SANGLAH GENERAL HOSPITAL BALI-INDONESIA - Wardhana, and, M.; Rusyati, L. M. (BALI MEDICAL JOURNAL, 2013)
Objectives: Pemphigus vulgaris (PV) is an autoimmune-blistering disease of the skin and mucous membranes caused by auto-antibodies against desmoglein-3 (Dsg-3) on the keratinocyte cell surface of squamous stratified epithelia. Pemphigus is a life-threatening autoimmune bullous disease resulting in the widespread denudation of skin and mucous membrane and severe impact of quality of life. The purpose of this study was to evaluate retrospectively the prevalence of pemphigus and to elucidate the clinical variants, clinical course, prognosis and quality of life (QOL) of pemphigus patients after discharge from hospitalized. Method: Observational non analytical retrospective study was conducted by observation of the medical records of all the newly registered patients with pemphigus at Sanglah General Hospital in Bali-Indonesia during the period of January 1995 and December 2002, and analyzed with regard to personal statistic, history of the diseases including onset, site of affected, symptoms, clinical diagnosis, severity, associated illness, therapy, and quality of life based on the Finlay’s methods. Results : During the 8-year periods studies, 33 pemphigus patients were admitted, represented 5.8 % of  all patients admitted in our in-patient ward during the periods. Our patients consist of female 20 patients (60.6 %) and male 13 patients (39.4 %). The most common of clinical type was pemphigus vulgaris 26 patients (78.78 %), followed by pemphigus foleaceous and pemphigus vegetans. Six patients (18.18 %) of 16 severe patients with severe condition at the clinical course of the diseases was death during the course of hospitalized. A number of 2 patients, in this study were observed with severe impact of quality of life. Conclusion: Our finding showed that pemphigus vulgaris is common type of our cases has a relatively high prevalence our hospital (5.8 %), and relatively high death rate (18.18 %). In our study, systemic corticosteroid was still applied until present for life saving drug for Pemphigus.
Keywords: Pemphigus, retrospective study, quality of life